The Influence of Credit Quality, Strong Tie and Bridge Tie on the Firm Performance: Mediating Effect of Supply Chain Management a - Zain Nahdi Baldina; Achsania Hendratmi (International Journal of Supply Chain Management, 2020)
The foremost purpose of the present study is to analyze the impact of credit quality, strong tie and bridge tie on the performance of Islamic banks in Indonesia. The goal of the current study also shows the investigation of the mediating role of supply chain management among the links of credit quality, strong tie, bridge tie and performance of Islamic banks in Indonesia. The data has been obtained by using the questionnaire method and smart-PLS has been executed for analysis. The results revealed that credit quality and strong tie has positively linked with the performance of Islamic banks in Indonesia. The results also exposed that supply chain management positively mediating among the links of credit quality, strong tie, bridge tie and performance of Islamic banks in Indonesia. These findings provided suitable grounds to the new studies who want to investigate this area in future along with the policymakers who develop the policies related to the supply chain and firm performance.